The effect of some nutrients and water quality parameters on the IN VITRO multiplication, longevity and survival of VIBRIO PARAHAEMOLYTICUS isolated from cage cultured fish - Chong Sen Mun @ Esther (Universiti Pertanian Malaysia, 2012)
Laboratory microcosms were employed to evaluate the effect of some selected water quality parameters and inorganic nutrients on the population of Vibrio parahaemolyticus.